Accessing information through internet - Nair, R. Raman (Ess Ess Publications, 2002)
Contents of material: 1/ Introduction. 2/ Hardware and sofware. 3/ Key to Windows. 4/ Internet services. 5/ Connecting to the internet. 6/ Information access 7/ Security and power to surf. 8/ Email and document transfer. 9/ Information retrieval. 10/ Search engines. 11/ Online reference books. 12/ Information online.